Effect of surface roughness of TiO2 films on short-circuit current density of photoelectrochemical cell of ITO/TiO2/ PVC-LiClO4/graphite - Rahman M.Y.A.; Salleh M.M.; Talib I.A.; Yahaya M. (2023)
This paper reports the effect of surface topography of titanium dioxide films on short-circuit current density of photoelectrochemical solar cell of ITO/TiO2/PVC-LiCLO4/graphite. The films were deposited onto ITO-covered glass substrate by screen-printing technique. The films were tempered at 300C, 350C, 400C, 450C and 500C for 30 min to burn out the organic parts and to achieve the films with porous structure. The surface roughness of the films were studied using scanning electron microscope (SEM). Current-voltage relationship of the devices were characterized in dark at room temperature and under illumination of 100 mW cm-2 light from tungsten halogen lamp at 50C. The device utilising the TiO2 film annealed at 400C produces the highest short-circuit current density and open-circuit voltage as it posses the smoothest surface topography with the electrolyte. The short-circuit current density and open-circuit voltage of the devices increase with the decreasing grain size of the TiO2 films. The short-circuit current density and open-circuit voltage are 0.6 ?A/cm2 and 109 mV respectively. 2004 Elsevier B.V. All rights reserved.